2020
DOI: 10.3389/fpubh.2020.596607
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Shelter-in-Place Orders on Social Distancing and the Spread of the COVID-19 Pandemic: A Study of Texas

Abstract: Objectives: We study how the state-wide shelter-in-place order affected social distancing and the number of cases and deaths in Texas.Methods: We use daily data at the county level. The COVID-19 cases and fatalities data are from the New York Times. Social distancing measures are from SafeGraph. Both data are retrieved from the Unfolded Studio website. The county-level COVID-related policy responses are from the National Association of Counties. We use an event-study design and regression analysis to estimate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…This rhetoric was found to be associated with lower perceived COVID-19 threat [25]. COVID-19 conspiratorial beliefs associated with less cooperation to safety guidelines [26]. By not participating in proven safety measures, such as wearing a mask, many people unnecessarily contracted the disease.…”
Section: Introductionmentioning
confidence: 98%
“…This rhetoric was found to be associated with lower perceived COVID-19 threat [25]. COVID-19 conspiratorial beliefs associated with less cooperation to safety guidelines [26]. By not participating in proven safety measures, such as wearing a mask, many people unnecessarily contracted the disease.…”
Section: Introductionmentioning
confidence: 98%
“…This is only an example of the caution that needs to be exerted before drawing inferences from open data that are of variable quality and sometimes wrongly interpreted. On the other hand, epidemiologic studies reported in this journal have progressed our understanding of the risk factors associated with SARS-CoV-2 transmission and COVID-19 fatal outcomes (13)(14)(15)(16)(17)(18)(19). Likewise, modeling studies have shed light on effective control measures and likely trajectory of the pandemic in various settings (20)(21)(22)(23).…”
Section: Use and Misuse Of Epidemiologic Surveillance Datamentioning
confidence: 96%
“…More detailed epidemiologic investigations revealed important determinants of epidemic spread at the local level by using diverse statistical models (17,18). De Ridder et al used a spatiotemporal cluster detection algorithm to monitor SARS-CoV-2 transmission dynamics in neighborhoods of Geneva until 30 April 2020 (17).…”
Section: Use and Misuse Of Epidemiologic Surveillance Datamentioning
confidence: 99%
See 2 more Smart Citations